2011
DOI: 10.1016/j.agee.2011.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Pollination services in the UK: How important are honeybees?

Abstract: Dear Downloader, Thank you for downloading this publication from our repository. The University of Reading is committed to increasing the visibility of our research and to demonstrating the value that it has on individuals, communities, organisations and institutions. To support us in this commitment, we are running a pilot project to find out more about the people who download information from the University of Reading website. The publication you have downloaded is part of this project. It would help us grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
247
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(258 citation statements)
references
References 42 publications
2
247
0
9
Order By: Relevance
“…This ties in with accumulating recent literature on the relative benefits of wild bees and of commercial honey bees, as pollinators of natural habitats and urban spaces (Lowenstein et al 2015;Hausmann et al 2016). Wild bees are also vital, and often better than Apis, as crop pollinators, with the importance of honeybees often over-emphasised in the past (see Breeze et al 2011;Garibaldi et al 2013). For example, halictid bees are important for melon (Rodrigo-Gomez et al 2016) and watermelon (Garantonakis et al 2016), bumblebees are important for blueberries (Button and Elle 2014) and several wild bees are better than managed honeybees at pollinating apples (Mallinger and Gratton 2015), although it is only a few relatively common solitary bee species that are crucial across crops in general (Kleijn et al 2015).…”
Section: Discussionmentioning
confidence: 74%
“…This ties in with accumulating recent literature on the relative benefits of wild bees and of commercial honey bees, as pollinators of natural habitats and urban spaces (Lowenstein et al 2015;Hausmann et al 2016). Wild bees are also vital, and often better than Apis, as crop pollinators, with the importance of honeybees often over-emphasised in the past (see Breeze et al 2011;Garibaldi et al 2013). For example, halictid bees are important for melon (Rodrigo-Gomez et al 2016) and watermelon (Garantonakis et al 2016), bumblebees are important for blueberries (Button and Elle 2014) and several wild bees are better than managed honeybees at pollinating apples (Mallinger and Gratton 2015), although it is only a few relatively common solitary bee species that are crucial across crops in general (Kleijn et al 2015).…”
Section: Discussionmentioning
confidence: 74%
“…For some important pollinator‐dependent crops grown in the UK, such as apple, solitary bees are more efficient pollinators than honeybees (Delaplane, Mayer, & Mayer, 2000; Garratt et al., 2014). As the cultivation of crops that depend on insect pollination continues to expand (Aizen, Garibaldi, Cunningham, & Klein, 2008), the conservation of solitary bee communities on farmland is important; it is estimated that current honeybee populations are capable of supplying just 34% of the pollination service demand in the UK (Breeze, Bailey, Balcombe, & Potts, 2011). The effectiveness of current wildflower mixes in supporting solitary bee foraging in the UK landscape remains a key knowledge gap and one that this study aimed to address, for cavity‐nesting solitary bees specifically.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, most of the credit has been given to domestic honeybees. However, recent studies have shown that wild pollinators are more important contributors to global crop pollination than previously assumed (Breeze et al 2011). Estimates for the UK indicate that managed honeybees (Apis mellifera) pollinate approximately no more than one third of the crops.…”
Section: Box 1: Crops That Depend On Insect Pollinationmentioning
confidence: 98%